Obstacles of PPKn Alumni in Getting a Job And its Relevance to the 2013 curriculum - Dewi Muryati; Endhah Charolyna; Yustia; Ahmad Saefulloh (JURNAL PENDIDIKAN, 2020)
This research aims to the obstacles faced by the alumni of the 2015PPKn study program in relation to the relevance of the 2013 curriculum tothe job needs of alumni.This research is qualitative descriptive with purposive samplingtechnique. Data collection which includes online structured interviewsconducted with questions that were arranged and linked and developedtheoretical literature. The subjects of this study were alumni of the 2015PPKn FKIP, University of Palangka Raya.The results showed that the obstacles experienced by alumni of the2015 PPKn Study Program were the lack of soft skills in preparingthemselves to apply for jobs, either as teachers or other jobs relevant to the discipline of knowledge that alumni have. The effort that needs to be done toovercome these difficulties is the optimization of work in the form of softskills or products that can be a selling point for the alumni themselves.